2008
DOI: 10.1177/0091270008315308
|View full text |Cite
|
Sign up to set email alerts
|

Are Literature References Sufficient for Dose Recommendations? An FDA Case Study of Efavirenz and Rifampin

Abstract: One of the numerous regulatory functions of the Food and Drug Administration (FDA) is the evaluation of drug-drug interactions and the determination of appropriate dose adjustments, if necessary, to ensure the safe and effective use of medications. The FDA considers several data sources when determining the significance of drug-drug interactions. The majority of dose adjustment recommendations are based on specific drug-drug interactions studies. The FDA reviews individual patient pharmacokinetic and safety da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The simulated effects of rifampicin co-administration on efavirenz treatment showed only a minor decrease of 16% (95% confidence interval [13][14][15][16][17][18][19] in efavirenz area under the concentration-time curve, of the same magnitude as what has been clinically observed (22%). Efavirenz exposure depended on CYP2B6 phenotype and bodyweight.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulated effects of rifampicin co-administration on efavirenz treatment showed only a minor decrease of 16% (95% confidence interval [13][14][15][16][17][18][19] in efavirenz area under the concentration-time curve, of the same magnitude as what has been clinically observed (22%). Efavirenz exposure depended on CYP2B6 phenotype and bodyweight.…”
Section: Resultsmentioning
confidence: 99%
“…Efavirenz steady-state oral efavirenz clearance was estimated as 12.6 l h -1 with concomitant rifampicin, which is somewhat lower than clinical data (17.2 l h -1 ). The simulations of continuous efavirenz administration predicted a mean decrease in efavirenz AUC of 16% [95% confidence interval (CI) [13][14][15][16][17][18][19] in the presence of rifampicin.The model predicted mean decreases in Cmax and Ctrough of 14 (95% CI 11-16) and 18% (95% CI 15-21), respectively.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review of published literature did not find adequate evidence to support a dose increase with rifampin coadministration because of current lack of understanding of the likelihood of under-or overdosing individuals (11). Prior drug-drug interaction studies failed to evaluate genetic contributions to the variability in the induction effect of rifampin (2,24), were performed in the setting of clinical care, where patients were receiving other antituberculous drugs in addition to rifampin, or did not have an appropriate control period or comparator group (13,20,25,35).…”
mentioning
confidence: 99%
“…Although effective pharmacological, clinical, immunological, and virologic responses have been reported with a 600-mg dose of EFV (11,22,27,28), the adequacy of this dose during concomitant treatment with RMP remains a matter of debate. In fact, after reviewing the current literature, the FDA concluded that the available data are insufficient to support definitive dosing recommendations for the coadministration of EFV and RMP (10). Differences in patients' body weights appear to cause further differences in exposure to EFV, raising the question of whether the EFV dose should be increased in people with higher body weights (20,26).…”
mentioning
confidence: 99%